TALE-bound QTL: a computational investigation of bacterial effector association with resistance quantitative trait loci in Oryza sativa - Sharkey, Jacob Emmett, author; Leach, Jan E., advisor; Huerta, Alejandra I., committee member; Nishimura, Marc, committee member; Roberts, Robyn, committee member (Colorado State University. Libraries, 2022)
Durable resistance to Xanthomonas oryzae pathovars oryzae (Xoo) and oryzicola (Xoc), which cause bacterial blight and bacterial leaf streak, respectively, is highly sought after in rice (Oryza sativa) due to the pathogens ability to impact maximum attainable yields. Regions of the rice genome associated with quantitative resistance to multiple strains of Xoo and Xoc, known as quantitative trait loci (QTL), were previously identified using a multi-parent advanced generation intercross (MAGIC) rice population and a combination of genome wide association studies and interval mapping. These QTL have been associated with decreased lesion lengths by Xoc and Xoo on rice. What remains unknown is the molecular basis for the induction of genes under these QTL during pathogen infection. Considering our biological question "what is the molecular basis for regulation of resistance QTL associated with Xoo and Xoc?", we predicted that part of the answer could be found by investigating the bacteria's direct interaction with the O. sativa genome. Upon infection, Xoo and Xoc injects the host with DNA-binding TALE (transcription activator-like effector) proteins. These effectors, when bound to their target plant gene promoter, induce gene transcription. We hypothesize that differential interactions of TALE with promoters of rice genes under the QTL lead to the resistant/susceptible phenotypes exhibited across varieties. To test this, we designed a pipeline that predicts TALE-regulated candidate genes involved in quantitative resistance. This pipeline identifies genes that meet three criteria: (1) the presence of a binding site for an X. oryzae TALE in the gene's promoter, a strong correlation between binding site presence, and disease phenotypes and overlap of the gene with a resistance QTL. We used this pipeline with genomic and phenotypic data for the eight MAGIC founders to identify candidate genes involved in resistance against seven Xoo and Xoc strains. Candidate genes identified include ones encoding a patatin-like phospholipase and multiple NB-ARC containing proteins such as the Mla1 protein. Here, we exploit the abundant genomic data for the rice-X. oryzae systems and the ability to predict direct associations between bacterial proteins and plant genomes, to propose a method that could streamline the identification of genes involved in quantitative resistance to TALE- harboring Xanthomonas.